To What Extent is it Possible to Respect the Principle of Autonomy in Pandemic Times? A New Approach to Bioethical Principles - Dieb Miziara Ivan; Silvia Molleis Galego Miziara Carmen (Journal of Public Health International, 2021)
Based on two fictitious cases of disregard for the rules to prevent the spread of Sars-Cov-2 in which individuals claim that their autonomy has been disrespected, in Brazil, the authors ask to what extent individual autonomy must be strictly respected and propose a new approach to the bioethics principles, so that they are applied with a view to public health and the common good.
Keywords: Autonomy